Aggregate Volatility Risk and Empirical Factors: An International Study. Issue 5 (9th April 2021) - Lee, Woongki; Park, James L.; Sohn, Bumjean
ABSTRACT: We study the aggregate volatility risk in international stock markets. We examine four regional (North America, Europe, Japan, and Asia Pacific) stock markets to see if the aggregate volatility risk is priced and find out its relationship with regional empirical factors. We find that the aggregate volatility risk is priced robustly across stocks in all regions but Japan. Within the intertemporal capital asset pricing model framework, we show that the aggregate volatility risk is closely connected with the momentum profits. Our theoretical framework coupled with the return and volatility spillover effects hints at an interesting explanation for the coexistence of global and local factors.